PRAKTIKALITAS MEDIA PEMBELAJARAN MATEMATIKA BERBENTUK VIDEO SIMULASI PADA SISWA SEKOLAH MENENGAH KEJURUAN - Fitri, Yuliani; Putri, Anike (Math Educa Journal, 2021)
This study was conducted due to the lack of audi visual learning aids in developing students’ understanding on two-variable linear equation. The aim of this study is to describe the practicality of developed medium, specially, video of simulation for learning mathematics in TAV students of X grade of SMK 5 Padang concerning two-variable linear equation. This developing study uses procedural development in accordance to Alessi and Trollip (2001), consisting of 3 steps; planning; design; and development. Practicality data of product gained through development phase by scoring teacher responded questionnaire and student responded questionnaire. The result of product testing shows that video of simulation is pratical to be used in learning mathematics.